Smart Health Monitoring Using Wearable Device Sensors: A Brief Review - Dibyendu Mandal; Sandip Bag; Sandip Bag (International Journal of Pharma and Bio Sciences, 2023)
Wearable technology is an emerging and indispensable area for health parameter monitoring that is expanding all year round for appraising, investigating, and treating critically ill patients significantly. As wearable technology develops and the demand for real-time analytic monitoring increases, researchers are urged to create more wearable monitoring devices. The newest generation of personal portable electronics is being lauded as comprising wearable monitoring systems. As material science, integrated circuit fabrication, industrial innovation, fabrication of integrated circuits, and structural design develop, wearable healthcare devices will usher in a new era for illness detection, treatment, and prevention. Numerous industries employ wearables, including agriculture, sports, and hospital navigation systems. In this study, the conceptual evolution of wearable gadgets and their usefulness in the field of personalised healthcare are examined. This study aims to present a futuristic examination of wearable health sensors and systems for smart, reliable health monitoring and rehabilitation.